Difference between revisions of "005 Sample Final A, Question 18"

From Math Wiki
Jump to navigation Jump to search
(Created page with "''' Question ''' Graph the following function, <center><math>f(x) = \left(\frac{1}{3}\right)^{x+1} + 1</math></center> <br> Make sure to label any asymptotes, and at least two...")
 
Line 4: Line 4:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Final Answers
+
! Foundations
 
|-
 
|-
|a) False. Nothing in the definition of a geometric sequence requires the common ratio to be always positive. For example, <math>a_n = (-a)^n</math>
+
|1) What is the basic graph of <math> f(x) = 3^{(x+1)} - 2</math>?
 
|-
 
|-
|b) False. Linear systems only have a solution if the lines intersect. So y = x and y = x + 1 will never intersect because they are parallel.
+
|2) How is the graph <math>g(x)=x+1</math> obtained from <math>f(x)=x</math>?
 
|-
 
|-
|c) False. <math>y = x^2</math> does not have an inverse.
+
|3) How is the graph <math>g(x)=(x-3)^2</math> obtained from <math>f(x)=x^2</math>?
 
|-
 
|-
|d) True. <math>cos^2(x) - cos(x) = 0</math> has multiple solutions.
+
|Answer:
 
|-
 
|-
|e) True.
+
|1) The basic graph is <math>y=3^x</math>.
 
|-
 
|-
|f) False.  
+
|2) The graph of <math>g(x)</math> is obtained by shifting the graph of <math>f(x)</math> up 1 unit.
 +
|-
 +
|3) The graph of <math>g(x)</math> is obtained by shifting the graph of <math>f(x)</math> to the right by 3 units.
 +
|}
 +
 
 +
 
 +
Solution:
 +
 
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
! Step 1:
 +
|-
 +
|We start with the basic graph of <math>g(x)=3^x</math>.
 +
|-
 +
|To get the graph of <math>f(x)</math> from <math>g(x)</math>, we shift the graph of <math>g(x)</math> down 2 and to the left by 1.
 +
|}
 +
 
 +
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
! Step 2:
 +
|-
 +
|Two ordered pairs are (-1,-1), and (0,1). There is a horizontal asymptote at <math>y=-2</math>.
 +
|}
 +
 
 +
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
! Final Answer:
 +
|-
 +
|To get the graph of <math>f(x)</math> from <math>3^x</math>, we shift the graph of <math>3^x</math> down 2 and to the left by 1.
 +
|-
 +
|Two ordered pairs are (-1,-1), and (0,1). There is a horizontal asymptote at <math>y=-2</math>
 +
|-
 +
|
 +
[[File:4_Sample_Final_5.png]]
 
|}
 
|}
  
 
[[005 Sample Final A|'''<u>Return to Sample Exam</u>''']]
 
[[005 Sample Final A|'''<u>Return to Sample Exam</u>''']]

Revision as of 10:50, 2 June 2015

Question Graph the following function,


Make sure to label any asymptotes, and at least two points on the graph.


Foundations
1) What is the basic graph of ?
2) How is the graph obtained from ?
3) How is the graph obtained from ?
Answer:
1) The basic graph is .
2) The graph of is obtained by shifting the graph of up 1 unit.
3) The graph of is obtained by shifting the graph of to the right by 3 units.


Solution:

Step 1:
We start with the basic graph of .
To get the graph of from , we shift the graph of down 2 and to the left by 1.
Step 2:
Two ordered pairs are (-1,-1), and (0,1). There is a horizontal asymptote at .
Final Answer:
To get the graph of from , we shift the graph of down 2 and to the left by 1.
Two ordered pairs are (-1,-1), and (0,1). There is a horizontal asymptote at

4 Sample Final 5.png

Return to Sample Exam